HELPING OLDER AFRICAN AMERICANS THRIVE: FROM DISPARITY TO EMPOWERMENT - Waites, C (Innov Aging, 2018)
African American elders are disproportionately victimized by systems, which relegate them to disparities in health, education, socio-economics and the social environment. As a result, avenues to promote successful aging and to promote awareness and empowerment are critical (Waites, 2012) (Ntiri & Stewart, 2009). A study was conducted to better understand some realities of aging for African American elders and to inform stratigies to help them thrive. An ecological perspective and wellness framework were employed to understand how elders conceived aging. Two focus groups with African American older adults, age 57 – 83 were conducted. The researchers applied Paulo Freire’s emancipatory literacy and engaged informants in discussing strategies for successful aging. These groups also provided information regarding strategies for service provision. Sessions were audio taped, transcribed and analyzed by the researchers using qualitative methods. Findings indicate that older African Americans want to maintain their independence and recognize that they may need some assistance as they age in place. They have observed, and were disturbed, that some elders define themselves by their disability and “don’t try,” they “give up” and isolate themselves. While many expressed feeling pushed aside by family and society they rejected the stereotypes regarding aging. They called for programs to empower African Americans to be proactive regarding their wellness and health care and for strategies that actively encourage engaged older adults to reach out to their less engaged peers. They also affirmed the need for approaches to enlighten younger generations about the “senior world,” and aging.